Effectiveness and safety of combined treatment with herbal medicines and palliative chemotherapy for advanced gastric cancer: A systematic review, and meta-analysis - Dong-Hyeon Kim; Soo-Dam Kim; Hyeong-Joon Jun; Eun-Bin Kwag; Sang-Won Shin; Hwa-Seung Yoo; So-Jung Park (Integrative Medicine Research, 2025)
Background: Advanced gastric cancer (AGC) is a leading cause of cancer-related deaths worldwide, with its treatment complicated by challenges such as high recurrence rates, severe side effects, and limited effectiveness of current therapies. Herbal medicine (HM) has emerged as an adjunct to palliative chemotherapy (PC), potentially improving tumor response and reducing side effects. This study conducted a meta-analysis to evaluate the effectiveness and safety of HM in palliative therapy for inoperable stage Ⅲ and Ⅳ AGC patients. Methods: Databases were searched until August 2023, encompassing 10 electronic databases, including PubMed, Embase, Cochrane Library, CNKI, and ScienceON. The inclusion criteria focused on randomized controlled trials (RCTs) combining herbal medicine with palliative therapy for patients with AGC. Primary outcomes assessed were tumor response rates, overall survival, adverse drug reactions (ADRs), and patients' quality of life (QoL). Results: In our analysis of 101 RCTs comparing PC alone to PC combined with HM, the meta-analysis demonstrated statistically significant improvements in overall response rate (ORR), disease control rate (DCR), survival rates, as well as a reduction in adverse drug reactions (ADRs) and an enhancement in quality of life (QoL) for patients receiving HM in combination with PC (p < 0.00001, I² = 0 %). Conclusion: The combination of HM with PC significantly enhances tumor response and survival rates while reducing overall adverse drug reactions (ADRs) and improving quality of life (QoL) in patients with stage Ⅲ and Ⅳ AGC. HMs not only improve the efficacy of PC but also help alleviate side effects, including myelosuppression, digestive symptoms, nausea, vomiting, diarrhea, liver and renal injuries, and neurotoxicity.Protocol registration: PROSPERO, CRD 42022354133.